A Finite-element Method Analysis of Electromagnetic Noise Absorption in a Coplanar Transmission Line Integrated with a Magnetic Film - 임상호; 한석희; 손재천 (한국자기학회, 2006)
A finite-element method is used to analyze loss generation and electromagnetic noise absorption characteristics of a coplanar waveguide transmission line integrated with a magnetic thin film. Parameters used in the analysis are the electrical resistivity of the magnetic layer and the thickness of both magnetic and insulating layers. The results indicate that L-C resonance is the main loss mechanism of the electromagnetic noise absorption.